Innovative Approaches for Pharmacology Studies in Pregnant and Lactating Women: A Viewpoint and Lessons from HIV - Ahizechukwu C. Eke (2020)
© 2020, The Author(s). Medication use during pregnancy in the absence of pharmacokinetic and safety data is common, particularly for antiretrovirals, as pregnant women are not usually included in clinical trials leading to drug licensure. To date, data are typically generated through opportunistic pregnancy studies performed in the postmarketing setting, leading to a substantial time-lag between initial regulatory approval of a drug and availability of essential pregnancy-specific pharmacokinetic and safety data. During this period, health care providers lack key information on human placental transfer, fetal exposure, optimal maternal dosing in pregnancy, and maternal and fetal drug toxicity, including teratogenicity risk. We discuss new approaches that could facilitate the acquisition of these critical data earlier in the drug development process, aiding clinicians and patients in making informed decisions on drug selection and dosing during pregnancy. An integrated approach utilizing multiple novel methodologies (in vitro, ex vivo, in silico and in vivo) is needed to accelerate the availability of pharmacology data in pregnancy and lactation.